Erasmus bilateral agreement for the academic years 2010-2013 Lifelong Learning Programme – Higher Education Erasmus between Universidad de Oviedo and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Co-operate in the activities within Lifelong Learning programme. - Subject area: Law.